PENGEMBANGAN MODEL PEMBELAJARAN KOGNITIF MORAL MELALUI MEDIA CERITA ANIMASI UNTUK MENINGKATKAN PERTIMBANGAN MORAL SISWA SEKOLAH DASAR - Aiman Faiz, - (2023)
Moral-related studies become a conversation that never ends. In moral studies, moral decision-making will determine one's actions. But of course moral decision-making needs to be based on mature moral considerations. The purpose of this study was to develop a moral cognitive learning model through the medium of animated stories to increase elementary school students' moral judgments and determine the effectiveness of this model. Researchers used a Research and development approach in developing this learning model. The results of the study show that the reality on the ground is that the cognitive-moral learning model is rarely applied by elementary school teachers. Therefore the researchers developed a moral cognitive learning model through animation media. Before the animation media was constructed, the researcher tested the reading content comprehension test instrument using the gap test on fifth grade students. The students' gap text test results obtained an understanding score above 60% which indicated that the text was suitable for use. The development continued with the validation of experts in the field of animation media on average 85%, linguists on average 90%, moral education experts on average 90% and developmental psychologists on average 85%. The material developed by the researcher refers to the lesson plan with sub-themes of events in life. In testing the effectiveness of the model at SDN 4 Kenanga, SDN 1 Tukmudal, SDN 2 Tukmudal and SDN 1 Babakan before being given treatment, students' tendencies varied between pre-conventional stage 1, pre-conventional stage 2, Conventional stage 1 and Conventional stage 2. After being given treatment in the form of animated story media in story 1 to story 5 tended students to become conventional stage 2 and slightly in conventional stage 1. It can be concluded that the moral cognitive learning model based on animated story media to increase the moral judgment of elementary school students in grade V is very effective to improve moral considerations of students.